Understanding the impact of environmental regulations on green technology innovation efficiency in the construction industry. (February 2021) - Zhang, Jingxiao; Ouyang, You; Ballesteros-Pérez, Pablo; Li, Hui; Philbin, Simon P.; Li, Zhaoling; Skitmore, Martin
Highlights: Different types of environmental regulations have differing effects on green technology innovation efficiency (GTIE). The relationship between command-and-control regulations and GTIE is U-shaped and there is some time lag. The relationship between market-based regulations and GTIE is inverted U-shaped and very significant. There is a negative linear relationship between voluntary regulations and GTIE, but only affect the current period. Abstract: In the current environmentally constrained context, deploying effective environmental regulations (ERs) to promote greener technologies is necessary. Green technology innovation efficiency (GTIE) reflects the efficiency of an industry's use of resources in the green technology innovation process. However, previous research has considered innovation as a black box regarding the potential contribution and diversity of ERs. In order to analyze the differential impacts of ERs on GTIE, this study classifies ERs into command-and-control, market-based and voluntary. By adopting China's 2000–2017 construction industry as a case study, this study analyzes GTIE evolution based on a network Epsilon Based Measure (EBM) model and analyze the impacts of ERs by Tobit Regression. Findings suggest that: (1) There is a significant disconnection between the Research & Development (R&D) and commercial application stages of green technology in construction industry. The construction industry is able to turn most R&D achievements into profits at the commercialization stage, but a large amount of R&D investment does not produce R&D achievements. (2) Different types of ERs have different impacts on GTIE, but their intended outcomes can only be achieved by a suitable combination of them.